(untitled) (Journal of Economics and Management Research, 2021)
This study is intended to explain the reality of the Algerian agriculture sector and food security before and during the COVID-19 period, and the focus will be on cereals production, where will describe the state of the sector and assess the potential impact of the shock on it. We concluded that the Algerian agriculture sector (cereals) are not outside the impact of COVID-19, especially, if the situation continues for a long time, With the knowing the Algerian agriculture far from registering and achieving acceptable levels of self-sufficiency in cereals, and to overcome this shortfall Algeria resorts to import from abroad